Obesity effect on a multimodal physiotherapy program for low back pain suffers: patient reported outcome. - Cuesta-Vargas, Antonio; González-Sánchez, Manuel (BMC, 2013)
Background: Several studies have linked obesity to the increased likelihood of lower back pain, but there are no studies focussing on the effectiveness of a multimodal physiotherapy programme (MPP) in obese subjects who suffer from chronic non-specific lower back pain (CNLBP). The aim of this study was to compare the effectiveness of an MPP in obese (G1) (body mass index (BMI):≥30) and non-obese (G2) (BMI:<30) patients with CNLBP. Methods: A quasi-experimental study with pre- and post-intervention evaluations of an MPP (lasting 8 weeks) was conducted on obese and non-obese patients with CNLBP. A total of 53 people were included in the study: G1, composed of 19 patients (10 men and 9 women) with a BMI of 33.75 and a mean age of 52.94 years, and G2, composed of 34 patients (18 men and 16 women) with a mean age of 49.19 years and an average BMI of 25.56. All patients were measured to calculate pre-intervention (baseline) and post-intervention (8 weeks) changes in disability (RMQ) and health related quality of life in physical and mental health component state of SF12 and quality of life (EQ-5D and EQ-VAS). Results: Post-intervention, non-obese group shown significant high improve than obese group in disability (RMQ: 4.00), physical component state of SF-12: (-7.26) and quality of life (EQ-VAS.: -10.49). Conclusions: In patients with CNLBP, a BMI more than or equal to 30 minimises the effects of an MPP lasting 8 weeks.
Keywords: Lumbago - Ejercicios terapéuticos; Obesidad - Prevención; Obesity; Low back pain; Physiotherapy; Disability; Health-related quality of life